R&D Plans, Expectations, and Uncertainty: Evidence from the COVID-19 Shock in Italy - Emanuele Brancati (Institute of Labor Economics (IZA), 2021)
This paper takes advantage of the COVID-19 outbreak to explore the determinants of firms' R&D choices around an exogenous shock. We make use of unique panel data on 7,800 Italian companies between January 2020 –right before the pandemic– and March of the same year –amid lockdown policies. We then exploit the revision in firms' research plans within this short-time window to test the impact of deteriorating expectations and uncertainty on firms' R&D choices. Our results show a dramatic effect of firms' expectations about future market conditions. In this regard, internationalized and innovative companies, which were particularly suffering the onset of the crisis, display a significantly higher probability of discontinuing research plans. Beyond the role played by expectations, innovative characteristics already in place are found to critically shape firms' reactions to the general uncertainty. Two main patterns emerge from our analysis. On the one hand, there is a strong degree of persistence in R&D choices for a small set of innovators with substantial past expenditure in in-house research activities. On the other, the COVID-19 shock especially jeopardized R&D plans of firms that recently started new research programs or newly innovative companies. We interpret such results as evidence that preexisting sunk costs increase the persistence of R&D choices after uncertainty shocks.
Keywords: O3; D22; D84; 330; firms; R&D; expectations; uncertainty; COVID-19